Overexpression of Interleukin-1α Suppresses Liver Metastasis of Lymphoma: Implications for Antitumor Effects of CD8+ T-cells. (April 2021) - Udagawa, Kazuhiko; Niki, Yasuo; Kikuchi, Toshiyuki; Fukuhara, Yusuke; Takeda, Yuki; Miyamoto, Takeshi; Matsumoto, Morio; Nakamura, Masaya
Interleukin (IL)-1 plays a key role in carcinogenesis, tumor progression, and metastasis. Although IL-1 may enhance the expansion of CD8+ T-cells, the pathological contribution of IL-1-activated CD8+ T-cells to tumor metastasis remains unclear. This study used a liver metastasis model of the EL4 T-cell lymphoma cells transplanted into human IL (hIL)-1α conditional transgenic (hIL-1α cTg) mice. Overproduction of hIL-1α suppressed both macroscopic and histological liver metastasis of EL4 T-cell lymphoma. The hIL-1α-induced inflammatory state increased the number of CD8+ T-cells both within and around metastatic tumors. Moreover, larger numbers of CD8+ T-cells showed greater infiltration of liver blood vessels in hIL-1α cTg mice than in control wild-type mice. Terminal deoxynucleotidyl transferase dUTP nick-end labeling staining of liver tissue from hIL-1α cTg mice indicated increased apoptosis of cells in the tumor. Localization of apoptosis cells resembled that of CD8+ T-cells. In addition, cytotoxicity assay showed that CD8+ T-cell counts from tumor-bearing hIL-1α cTg mice correlated with cytotoxicity against EL4. In summary, IL-1α suppresses lymphoma metastasis, and IL-1α-activated CD8+ T-cells may play important roles in inhibiting both tumor metastasis and metastatic tumor growth: